Synthesis and Characterization of Co (II), Ni (II), Cd (II) and Cu (II) Complexes of Bis-Schiff Bases obtained from 1,8-Diaminonaphthalene - Turan, Nevin; Sekerci, Memet (Chem Soc Pakistan, 2009)
The present study deals with the preparation of Schiff base and its chelates with some transition metal ions Co (II), Ni (II), Cu (II) and Cd (II). The ligand was obtained by condensation of 1,8-diaminonaphthalene with salicylaldehyde. The ligand and its complexes have been characterized by elemental analyses, IR, H-1-NMR, UV-Vis. molar conductance and magnetic susceptibility. The analytical, spectral and magnetic data support the mononuclear formulations of these complexes with M/L 1:1. The Co (II) and Ni (II) complexes of ligand are proposed to be square-planar, while the Cu (II) and Cd (II) complexes are proposed to be tetrahedral.
Keywords: Zn(Ii) Complexes; Cu(Ii); Ni(Ii); Co(Ii); Mn(Ii)